Body, Scale, and Space: Study on the Spatial Construction of Mogao Cave 254 - Weiqiao Wang; Aibin Yan (Religions, 2023)
This article focuses on the relationship between body, scale, and space, as revealed in Mogao Cave 254 in Gansu Province. Three topics, namely, body scale, pilgrim behavior, and time–space perception, are discussed. A space model based on mapping and measurement by former scholars is created to facilitate and visualize the analysis of the body scale of the cave space; the restriction of body scale suggests certain pilgrim behavior in the cave, whereas the occurrence of body behavior results in perception in the dimension of time. How time and space are related must be understood to comprehend the motif of Buddhist expression. This study is an architectural approach to spatial analysis that integrates the design, construction, and use phases through the scale, behavior, and perception dimensions. It is dedicated to broadening and enriching the cognitive dimensions of the space value of Mogao caves to reveal the original value of caves as religious spaces and completely preserve their material and invisible cultural heritage.